1994
DOI: 10.5951/jresematheduc.25.5.0495
|View full text |Cite
|
Sign up to set email alerts
|

Academically Talented Students' Achievement in a Flexibly Paced Mathematics Program

Abstract: Third- through sixth-grade mathematically talented students (n = 306) enrolled in a flexibly paced mathematics course made achievement gains far beyond the normative gains expected over a one-year period. When compared to students several grade levels higher, these highly able students gained as much as 46 percentile points from pre- to posttesting. Above-grade-level testing revealed that the students possessed a wide range of mathematics knowledge prior to entering the course with some students scoring at exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Slavin (1987) found a median effect size of .45 for betweenclass grouping, while Rogers (1991) noted average effect sizes of .34. Additionally, Mills, Ablard, and Gustin (1994) found large effect sizes (ES -2.4 SD) for fifth graders enrolled in a betweenclass, flexibly-paced mathematics course with appropriate curricular adjustment.…”
Section: Research On Grouping Practicesmentioning
confidence: 95%
“…Slavin (1987) found a median effect size of .45 for betweenclass grouping, while Rogers (1991) noted average effect sizes of .34. Additionally, Mills, Ablard, and Gustin (1994) found large effect sizes (ES -2.4 SD) for fifth graders enrolled in a betweenclass, flexibly-paced mathematics course with appropriate curricular adjustment.…”
Section: Research On Grouping Practicesmentioning
confidence: 95%
“…High achievers differ in advanced reasoning when an above-grade-level test with a high enough ceiling is administered. Students in the top 3% on a grade-level achievement test can range widely, from the 1st through the 99th percentile, on an above-grade-level standardized test of verbal and mathematical reasoning (e.g., Mills, Ablard, & Gustin, 1994). For example, the Scholastic Aptitude Test (SAT) is often used to distinguish among high-achieving middle-school students for selection into challenging summer courses (Mills, 1992;Stanley, 1977).…”
Section: University Of Maryland Baltimore Countymentioning
confidence: 99%
“…The Carnegie Mellon Institute for Talented Elementary and Secondary Students (C-MITES; Carnegie Mellon University), TIP, CTD, and the Belin and Blank International Center for Gifted Education and Talent Development (University of Iowa) offer gifted third through sixth graders the EXPLORE test, a test developed by ACT in 2001 for eighth graders (see Lupkowski-Shoplik et al, 2003). Talent search methods have been shown to be effective at identifying academic talent in elementary students (e.g., Colangelo et al, 1994;Lupkowski-Shoplik & Assouline, 1993;Lupkowski-Shoplik & Swiatek, 1999) and providing them with challenging educational experiences (e.g., Mills, Ablard, & Gustin, 1994).…”
Section: Development Of the Talent Search Modelmentioning
confidence: 99%
“…Subsequent accelerative math classes have further demonstrated that both elementary students (Mills et al, 1994;Moore & Wood, 1988) and adolescents (e.g., Bartkovich & Mezynski, 1981;Mills et al, 1992;Stocking & Goldstein, 1992) who score well on abovelevel mathematics tests are able to learn advanced math quickly and well. Some of the academic benefits of these programs, especially those relating to the continuation of math acceleration after program participation, appear to be particularly strong for girls (Olszewski-Kubilius, 1998a).…”
Section: Talent Search Educational Programsmentioning
confidence: 99%